Biogenic volatile organic compounds emissions at high temperatures of common plants from Mediterranean regions affected by forest fires. (September 2014) - Courty, Léo; Chetehouna, Khaled; Lemée, Laurent; Fernandez-Pello, Carlos; Garo, Jean-Pierre
Vegetal species emit biogenic volatile organic compounds at elevated temperatures. Because of their combustibility, biogenic volatile organic compounds can modify the wildland fires propagation dynamics, changing them from a moderate behavior to an explosive propagation. This phenomenon is known as an accelerating forest fire. The origin of such phenomena can be the accumulation of biogenic volatile organic compounds in concentrations close to their lower flammability limit in seasons where the plants are themselves very flammable. There is a lack of information on the biogenic volatile organic compounds emissions of vegetal species typically found in wildland fires at temperatures higher than ambient temperature. In this work, we used a flash pyrolysis device linked to a gas chromatograph/mass spectrometer to investigate experimentally the biogenic volatile organic compounds emissions of Thymus vulgaris, Lavandula stœchas, and Cistus albidus between 70°C and 180°C. High amounts of terpenoid compounds were found, except for C. albidus emissions, including thymol, l-fenchone, and 3-hexen-1-ol. The information provided in this work could help to improve the characterization of thermal degradation of vegetal fuels and to incorporate the biogenic volatile organic compounds combustion in physical forest fires models. They also show that under the right circumstances, biogenic volatile organic compounds from these vegetal species could contribute to the development of an accelerating forest fire.